Economic Contribution of Home-stay in Nepal - Malla Thakuri, Indra Bahadur; Nepal, Govinda (Journal of Advanced Academic Research, 2017)
Home-stay is new model of tourism development in Nepal which provides an excellent opportunity to share, see and feel the diverse countryside lifestyle, local culture, and tradition. It promotes the rural economy through the promotion of rural tourism. The article aims to assess the economic contribution of home-stay entities of Nepal, based on the descriptive and exploratory design. Data were collected from the 102 home-stay entities of Lamjung, Tanahu and Nawalparasi districts. Statistical result shows that there is a significant increase in income and expenditure of local people in all sample study areas. It is found that majority of respondents have managed their household expenditure from the income of home-stay entities. The income status of Nawalparasi district is better than in the other two districts whereas the expenditure of Tanahu district is higher than in the other two districts. It indicates the better economic status of Nawalparasi district. All home-stay operators have reported the increment in their savings, which directly contributes to the improvement in their economic status. However, it is also found that there is a need to improve the quality of service to increase the flow of local and foreign tourists to increase the income of home-stay operators. Journal of Advanced Academic Research Vol. 3, No.3, 2016, page:1-10